(untitled) (Medical Forum Monthly, 2024)
Objective: This study aims to determine the obstetrical correlates and outcome of birth related Erb’s palsy. Study Design: Retrospective cohort study. Place and Duration of Study: This study was conducted in Obstetrics & Gynaecology and Orthopedics & Traumatology Departments of Khyber Teaching Hospital Peshawar from Dec 2004 to Nov 2009. Materials and Methods: Hospital records from Dec 2005 to Nov 2010 were searched. A cohort of all cases of birth related Erb’s palsy over a 5 year period was recorded. Birth records of cases were obtained. Cases were contacted and called for followup and assessment of functional outcome from Jan through March 2013. Results: A total of 30,367live births were recorded during the study period out of which there were 28 cases of obstetrical Erb’s palsy.Their birth records revealed that 27 were delivered vaginally and only 1 through cesarean section. In 17 cases delivery was complicated by shoulder dystocia out of which 10 mothers were diabetic. Mean weight at birth was 3.8 kg. All cases were managed conservatively. Twenty five cases presented for follow up. Twenty cases had no residual functional deficit. Five children had some form of functional deficit present. Conclusion: Erb’s palsy is seen more commonly in births complicated by shoulder dystocia and in diabetic mothers with high birth weight babies. Conservative management is effective but regular follow up is needed to pick up those cases that require surgical intervention to prevent lifelong handicap.